Analisis Karakteristik Material Baja dengan Metode Digital Image Correlation (DIC) - Suswanto, Budi; Iranata, Data; Septiarsilia, Yanisfa (Department of Civil Engineering, Diponegoro University, 2024)
The use of steel materials in building construction opens new opportunities for sustainable development, as steel exhibits corrosion resistance, durability, and reliability in terms of strength and ductility. Digital Image Correlation (DIC) is non-contact technique in which digital images of the surface of a test object are captured using high-resolution cameras. This study conducted measurements of strain distribution on the specimen's surface using the DIC method throughout the entire tensile testing process. The study particularly focuses on examining changes in strain distribution during the melting phase and the local deformation phase leading to fracture. In this research, a comparison will be made between the load-displacement curves obtained from experimental laboratory testing and the results analyzed using the DIC method for SS400-grade steel material. Based on the results of the tensile test and DIC analysis that have been conducted, conclusions have been drawn in the research. The tensile test results of SS400 steel material with a thickness of 6 mm, 8 mm, 10 mm, and 12 mm meet the quality requirements in the tested specification standards, and the results of the force-displacement curve between the experimental test results and the DIC method obtained a minimum deviation with a value below 10%,. Therefore, it can be concluded that the DIC method exhibits a reasonably good level of accuracy, making it suitable for validating the results of experimental tests.